Does corporate governance affect earnings management? - Nahed Habis Alrawashedh; Bilal Nayef Zureigat; Badi Salem Rawashdeh; Omar Zraqat; Lina Fuad Hussien (Heritage and Sustainable Development)
This study aims to analyze the effect of different corporate governance mechanisms on earnings management by focusing on Jordanian firms. As such, the study utilized data, and regression analysis of the scores included the coefficients of various corporate governance factors such as leverage, size, cash flow, firm growth, board size, board independence, and managerial ownership to determine the enjoyed effect on earnings management. The results show the significant correlation between regulations and corporate governance and its effects on earnings management. The coefficient of leverage, board size, board independence, and managerial ownership are statistically significant, signaling their effectiveness in maintaining low levels of earnings management; while high levels of cash flow are linked with high earnings management and constraints on the manager’s discretion, thus reducing earnings decision-making. Thus, it is seen that the role of corporate governance is crucial to ensure financial examination, which also serves to inform policymakers, stakeholders, and the public in Jordan and other democratic countries, and researchers to ensure fairness in accounting practice and that EM is reduced to the minimum.